Implementing Mass Customization Using SAP Variant Configuration and a 3D Printer - Paulraj, Thileepan (My University, 2014)
The process of manufacturing customized products at the efficiency of mass production is called mass customization manufacturing. In order to implement mass customization a product configurator, a well-planned configurable product platform and a flexible manufacturing technology are essential. As 3D printers are becoming more and more popular it is evident that they act as very flexible factories that could manufacture any object. This thesis tries to find out how 3D printers and product configurators could be combined to implement mass customization manufacturing. The system created in this thesis manufactures configurable motorcycles whose configuration model is maintained in SAP-ERP system. A product configurator built using SAP Variant configuration allows the user to configure a variant of the motorcycle according to their needs using the configuration model. This configured variant is manufactured using a 3D printer. Qualitative methods are used to gain knowledge and understanding about mass customization and SAP Variant configuration from books, scientific articles and software development forums. Using this knowledge the system is implemented which could manufacture approximately 23 different types of motorcycles customized by the user. The users who configure and manufacture the motorcycles also get hands-on knowledge about basic business processes in SAP ERP related to production planning (PP) and logistics (LO) modules and understand how information flows in the ERP system with respect to mass customized manufacturing.
Keywords: Mass Customisation; Product configurator; 3D Printing; SAP Variant Configuration; Configurable products; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|; fi=Digitaalinen media|en=Digital media|